KOMPETENSI PETERNAK AYAM RAS PEDAGING DI DESA CIBITUNG KULON KECAMATAN PAMIJAHAN KABUPATEN BOGOR - Helvi Yanfika; Moch Afandi Suprayitno (Jurusan Agribisnis Fakultas Pertanian Universitas Sultan Ageng Tirtayasa, 2019)
Breeders in Cibitung Kulon Village, Pamijahan District of Bogor Regency were farmers who implemented the partnership system. The breeders were plasma breeders with proprietary cages in capacity of 15,000 to 70,000 chickens. Under these conditions, it was important for all owners of the cage as the plasma to be able to manage the availability of feed and other livestock production to prevent any delay in feeding and make sure provision of the appropriate dosage of vitamins regularly as what was happened in independent breeders. Therefore, the competence of independent farmers in managing livestock business, and the factors associated with the level of farmers competence were described in descriptive analysis and analysed by statistical test of Spearman’s Rank. Noted that the farmers in this study were in the productive age where the majority were high school graduated, owned cages with area of 1000-1500 m2, while the role of extensions were quite well. The level of competence of broiler breeders in Cibitung Kulon village was still not very good, and the factors related to the competence of livestock breeders in running the broiler enterprise include age, length of the business running and the area of cage. While the level of education and the role of the extension were not related.